2019
DOI: 10.1111/are.14063
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of immune‐related genes in Pacific white shrimp, Litopenaeus vannamei, previously reared in biofloc and challenged with Vibrio harveyi

Abstract: This study aimed to evaluate possible modification of some immune‐related genes (hemocyanin, alpha2‐macroglobulin, prophenoloxidase and penaeidin3a) at the transcriptional level and signs of disease and mortality in Litopenaeus vannamei previously reared in biofloc and challenged with different Vibrio harveyi densities (103–108 CFU per ml). Gene expression was up‐ or downregulated based on bacterial density, indicating that defence mechanisms were activated to remove the pathogen. The genes analysed were not a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 53 publications
(68 reference statements)
0
3
0
Order By: Relevance
“…Our results indicate that the hemocyanin gene expression in the hepatopancreas significantly increased in the SCB treatment more than in the RS and RB treatments, and a significant difference was observed between 1.5 and 3 months. Similarly, Aguilera‐Rivera et al (2019) found that L. vannamei cultured in biofloc and infected with Vibrio harveyi exhibited an increase in the hemocyanin gene.…”
Section: Discussionmentioning
confidence: 89%
“…Our results indicate that the hemocyanin gene expression in the hepatopancreas significantly increased in the SCB treatment more than in the RS and RB treatments, and a significant difference was observed between 1.5 and 3 months. Similarly, Aguilera‐Rivera et al (2019) found that L. vannamei cultured in biofloc and infected with Vibrio harveyi exhibited an increase in the hemocyanin gene.…”
Section: Discussionmentioning
confidence: 89%
“…The first strand cDNA was generated at 59°C for 50 min. Then, the designed primers designated in this experiment, including the Peroxiredoxin ( Prx ), Prophenoloxidase ( PPO1 ), p53-like protein isoform delta ( p53 ), and hemocyanin subunit L5 ( L5H ) genes, were presented in Table 2 and prepared for q-RT-PCR estimation, which was conveyed into a fluorometric iQ5 thermocycler (Bio‐Rad ® ) following the Aguilera‐Rivera et al [ 51 ] guidelines and applying the gene β ‐actin as the housekeeping gene [ 52 ].…”
Section: Methodsmentioning
confidence: 99%
“…At the end of the feeding trial, three equal pools of independent samples of each five L. vannamei shrimp (whole animals) were collected, washed twice with PBS (137 mM NaCl, 2.7 mM KCl, 8 mM Na 2 HPO 4 , 1.46 mM KH 2 PO 4 , and pH 7.4), and stored in RNA later 1 reagent (Sigma-Aldrich 1 ; 1w:5v) at-20˚C as ascribed by the procedure of Goncalves et al [50]. The total RNA extraction and quantitative real-time PCR followed the method of Aguilera-Rivera et al [51]. Briefly, the TRIzol reagents protocol (TRIzol © ; Life Technologies) was applied to extract the total amount of RNA then the obtained extraction was quantified at 260 and 280 nm using a NanoDrop spectrophotometer (Thermo Scientific).…”
Section: Immune-related Gene Expressionsmentioning
confidence: 99%